Insights of probiotics as an alternative medicine for cancer therapy, mechanism, and applications - Sourik Mukherjee; Dharmender Kumar; Dipanjan Guha (Medicine in Microecology)
Probiotics are microbes associated with a wide range of health benefits and modulate gut flora by releasing effector molecules. The efficacy of probiotics at various stages of cancer treatment has been well demonstrated. Probiotics can increase the potency of cancer-based immunotherapy, which can be administered before, during, or post-phase therapy. The consumption of probiotics among cancer patients can minimize the detrimental effects of chemotherapy and act as a potential tool for cancer therapy. Genetically engineered probiotics can express specific antigens that can combat cancer and deadly pathogens. These essential features of probiotics can be utilized in cancer treatment and for other applications. This review aims to provide updated information on the mechanism of action of probiotics and their applications in cancer therapy. Moreover, a few other significant applications like; antioxidative therapy, biotechnology-based improvement, and developing potent probiotic strains for effective cancer treatment are also discussed.